Repetitive elements in genomes of parasitic protozoa. - Wickstead, B; Ersfeld, K; Gull, K (2003)
Repetitive DNA elements have been a part of the genomic fauna of eukaryotes perhaps since their very beginnings. Millions of years of coevolution have given repeats central roles in chromosome maintenance and genetic modulation. Here we review the genomes of parasitic protozoa in the context of the current understanding of repetitive elements. Particular reference is made to repeats in five medically important species with ongoing or completed genome sequencing projects: Plasmodium falciparum, Leishmania major, Trypanosoma brucei, Trypanosoma cruzi, and Giardia lamblia. These organisms are used to illustrate five thematic classes of repeats with different structures and genomic locations. We discuss how these repeat classes may interact with parasitic life-style and also how they can be used as experimental tools. The story which emerges is one of opportunism and upheaval which have been employed to add genetic diversity and genomic flexibility.